The Effect of Recruitment on Employee Performance Mediated by Job Placement - Irianawati, Irianawati; Ibrahim, Muhdi B. Hi; Irawan, Andri (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study aims to evaluate the effect of recruitment on employee performance with job placement as a mediating variable at Tk II Marthen Indey Hospital. Research Design and Methodology: This study uses a quantitative approach with explanatory research. The sample consisted of 137 non-military and non-ASN casual employees (KHL) at Tk II Marthen Indey Hospital, selected through the Simple Random Sampling method. Data was collected using a questionnaire on a 1-10 interval scale. Data analysis was conducted using Structural Equation Modeling (SEM) with the AMOS version 24.00 program. Findings and Discussion: The results show that recruitment significantly affects employee performance, and job placement is a significant mediator in this relationship. The z value of the Sobel test of 10.598 indicates that job placement can significantly mediate the effect of recruitment on employee performance. This result supports the hypothesis that effective recruitment must be followed by proper job placement to achieve optimal employee performance. Implications: This study makes an essential contribution to understanding the mediating role of job placement in the relationship between recruitment and employee performance. The findings provide practical insights for hospital management to improve recruitment and job placement processes and offer recommendations to improve operational efficiency and the quality of healthcare services. This study also provides a foundation for further research by expanding the scope and using a mixed approach to gain a more comprehensive understanding.